La lutte contre le néocolonialisme : L’impact des pensées politiques de Kwame Nkrumah - GERYVILLE, Zohra (La Revue d’Histoire Méditerranéenne, 2024)
In the immediate aftermath of the Second World War, the colonial trends of the eighteenth and nineteenth Century began to decline, and the Africans achieved their freedom. Though the African states achieved independence in politics, they remained dependent on their colonial masters, both economically and socio-culturally. Hence, colonialism as the main agency of imperialism appeared again but with a new face called neo-colonialism. To combat this dangerous phenomenon in the African continent, Nkrumah delved into several solutions. He referred to the African unity and the non-alignment as two prerequisite policies to eradicate the neo-colonial system. The present work attempts to examine in details these anti-imperialist policies, but prior to this, it is important to discuss the spread of neo-colonialism in Africa. Key words: Kwame Nkrumah; neo-colonialism; African unity; non-alignment